2008
DOI: 10.1007/s10661-008-0318-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of porous check dam location on fine sediment retention (a case study)

Abstract: This study was carried out to evaluate the influence of porous check dam location on the retention of fine sediments in the Droodzan watershed in Southern Iran. Five long streams with several porous check dams that were more than 27 years old were studied. In each stream three check dams: at the very upstream section, at the middle section and at the far downstream section were selected for analysis. A number of samples from trapped sediments and from the undisturbed soils in the stream banks (adjacent to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 7 publications
3
30
0
Order By: Relevance
“…Ran et al (2008) showed that check dams are the most effective soil conservation measures to rapidly reduce the amount of coarse sediment (grain size d ≥ 0.05 mm) entering the major rivers. Hassanli et al (2009) found that the portion of clay and silt trapped by porous check dams decreased from the downstream sections toward the upstream sections. The check dams located at the far downstream sections were more efficient at trapping fine sediment than those located at the middle sections and the upstream sections.…”
Section: Introductionmentioning
confidence: 97%
“…Ran et al (2008) showed that check dams are the most effective soil conservation measures to rapidly reduce the amount of coarse sediment (grain size d ≥ 0.05 mm) entering the major rivers. Hassanli et al (2009) found that the portion of clay and silt trapped by porous check dams decreased from the downstream sections toward the upstream sections. The check dams located at the far downstream sections were more efficient at trapping fine sediment than those located at the middle sections and the upstream sections.…”
Section: Introductionmentioning
confidence: 97%
“…Hassanli et al (2009) stated that grain size distribution of sediments deposited behind check dams depends on the type of the sediments transported and the performance of the check dams in trapping the sediments. In this study, the check dam is a solid dam where both water and sediments are trapped.…”
Section: Sediment Size and 137 Cs In Check Dammentioning
confidence: 99%
“…Therefore, check dams are actually multifunctional landscape units that can also trap huge amount of carbon in sediments. They have been used globally across various climate conditions such as the semiarid west Asia and Mediterranean region as well as humid European mountains (Wohl, 2006;Castillo et al, 2007;Hassanli et al, 2009). The carbon retention effects of these units cannot be neglected both for functional appraisal on check dams and their potential impacts on carbon cycling.…”
Section: Carbon Retention Enhancing the Multi-functionality Of Check mentioning
confidence: 99%
“…Check dams are manmade hydrological engineering structures built across drainage channels (Zeng et al, 2009). Although usually constructed with objectives of soil erosion control, their functions can be multi-dimensional such as soil and water retention, ground water recharge, water harvesting and supply, gully and slope stabilization, control of debris flow, regulation of river channel morphology, improvement of habitat conditions for vegetation restoration (Heede, 1979;Balooni et al, 2008;deWolfe et al, 2008;Ran et al, 2008;Bombino et al, 2009;Hassanli et al, 2009;Garg et al, 2011). Hence, check dams are actually multi-functional landscape units.…”
Section: Introductionmentioning
confidence: 99%